Collective action in institutional entrepreneuirship: The case of a government agency - Pimentel, L.; Major, M.; Cruz, A. (Emerging Science Journal, 2023)
This paper seeks to analyse how and why divergent institutional change occurred in a government agency. While there is evidence of research on the concept of collective action and involvement in the literature on institutional entrepreneurship, the focus has been at the macro and field levels, with scarce attention being given to the topic at the micro and organizational levels. This study addresses this gap in the literature, drawing on the institutional entrepreneurship process model of Battilana, Leca and Boxenbaum (The Academy of Management Annals, 2009), in combination with literature on collective action. The methodology involved a longitudinal case study, in which data were collected through extensive interviews and documentation analysis. Based on findings showing that the divergence change process could not be achieved without the support of organisational collective involvement, a refined version of the Battilana, et al. entrepreneurship model is proposed.